2013
DOI: 10.1177/0020872813477880
|View full text |Cite
|
Sign up to set email alerts
|

The role of self-help groups in post-tsunami rehabilitation

Abstract: This article provides an analysis of the importance of self-help groups for women in post-tsunami rehabilitation efforts in Tamil Nadu, India. The finding is one of eight key themes identified in a larger study of the long-term social, economic and gender implications of post-tsunami rehabilitation work. While self-help groups were reported as having provided women with a measure of new social and economic opportunities, status and power, little evidence existed for a substantial reduction of poverty levels or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Details of each study and their special features were reported regarding authors, year, study type, vulnerable group, sample size, type of rehabilitation, setting and duration of rehabilitation, disaster type, and main concepts. The studies were mainly conducted in Asian countries and United States, including India, [15,19,20,[25][26][27]31] China, [18,22,23,34,36,37] Pakistan, [16,28,30] Iran, [13,17,21] Indonesia, [29,32] Sri Lanka [35] and United States. [14,24,33] The results of the studies showed that 56% of the studies are about rehabilitation programs for women, 32% is for children, 24% is for elderly, and 16% is for disabled people.…”
Section: Demographicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of each study and their special features were reported regarding authors, year, study type, vulnerable group, sample size, type of rehabilitation, setting and duration of rehabilitation, disaster type, and main concepts. The studies were mainly conducted in Asian countries and United States, including India, [15,19,20,[25][26][27]31] China, [18,22,23,34,36,37] Pakistan, [16,28,30] Iran, [13,17,21] Indonesia, [29,32] Sri Lanka [35] and United States. [14,24,33] The results of the studies showed that 56% of the studies are about rehabilitation programs for women, 32% is for children, 24% is for elderly, and 16% is for disabled people.…”
Section: Demographicsmentioning
confidence: 99%
“…[14,24,33] The results of the studies showed that 56% of the studies are about rehabilitation programs for women, 32% is for children, 24% is for elderly, and 16% is for disabled people. Each study included more than one [29] (2008) + --+ + -+ + + -6/10 Rathore et al [30] (2008) + --+ + --+ + + 6/10 Bazeghi et al [17] (2010) + ---+ --+ -+ 4/10 Ni et al [34] (2013) + + + ----+ + -5/10 Xiao et al [23] (2011) + -+ ---+ + --4/10 Li et al [22] (2012) + + -----+ + -4/10 Tan et al [25] ( [14] (2011) + + -----+ --3/10 Bazeghi et al [17] (2010) + ---+ --+ -+ 4/10 Mansoor et al [16] (2013) + + --+ -+ + + + 7/10 Larson et al [15] (2015) + + -+ + --+ -+ 6/10 Huang et al [18] [11,12] Abbreviations: yes (+), no (-); World J Emerg Med, Vol 8, No 4, 2017 vulnerable group. The mean of the period of physical, psychological, social, and economic rehabilitation programs was about 7.3 months varying from 1 week to 50 months, which were based on the type of the disaster and the countries where the disaster occurred.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hazard refers to the actual physical process involved, while vulnerability is the compounded effect of the exposure and susceptibility of people and their assets to the impact of the hazard, as well as their capacity to anticipate, cope, and recover (Wisner et al, 2003). The most socially excluded and economically insecure in any society or community are least able to access or control resources needed before, during, and in the aftermath of a disaster (Larson et al, 2013). The term 'vulnerability' is used to understand how one's status, or social location can influence different impacts of natural hazards.…”
Section: Vulnerabilitymentioning
confidence: 99%